Cryptanalysis and improvement of a user authentication scheme for wireless sensor networks using chaotic maps. Issue 6 (19th October 2020) - Kumar, Devender; Chand, Satish; Kumar, Bijendra
Abstract : One of the challenging issues in wireless sensor networks (WSNs) is to provide secure communication as the channel used is wireless. User authentication is a mechanism that is used to provide secure communication. The authors analyse the security of a recent authentication scheme for WSNs and show that it is not resistant to smart card loss, insider, and denial of service attacks besides the user traceability problem. Here, they design an improved user authentication scheme using the chaotic maps for WSNs. The chaotic maps‐based public key cryptosystem helps a scheme to consider a large integer as the secret key rather than a large prime number and makes it fast. They show its formal security analysis using the random oracle model. They also analyse its security informally to show that it is resistant to various known attacks. They show that their scheme offers more security features than the existing schemes.